1999
DOI: 10.1006/dbio.1999.9479
|View full text |Cite
|
Sign up to set email alerts
|

The nieuwkoid/dharma Homeobox Gene Is Essential for bmp2b Repression in the Zebrafish Pregastrula

Abstract: Dorsoventral specification of the zebrafish gastrula is governed by the functions of the dorsal shield, a region of the embryo functionally analogous to the amphibian Spemann organizer. We report that the bozozok locus encodes the transcription factor nieuwkoid/dharma, a homeobox gene with non-cell-autonomous organizer-inducing activity. The nieuwkoid/dharma gene is expressed prior to the onset of gastrulation in a restricted region of an extraembryonic tissue, the yolk syncytial layer, that directly underlies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 67 publications
3
56
1
Order By: Relevance
“…Here, we report the isolation and characterization of a zebrafish admp homologue. We show that its expression is posi-tively regulated by the Bmp repressor Boz (Koos and Ho, 1999;Ryu et al, 2001), but that Admp itself has effects opposite to those of Boz. Thus, the phenotype of boz mutants can be phenocopied by overexpression of admp, whereas boz overexpression phenocopies traits of admp morphants.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Here, we report the isolation and characterization of a zebrafish admp homologue. We show that its expression is posi-tively regulated by the Bmp repressor Boz (Koos and Ho, 1999;Ryu et al, 2001), but that Admp itself has effects opposite to those of Boz. Thus, the phenotype of boz mutants can be phenocopied by overexpression of admp, whereas boz overexpression phenocopies traits of admp morphants.…”
Section: Introductionmentioning
confidence: 81%
“…Studies in Xenopus and zebrafish have demonstrated that Bmps act as morphogens inducing ventral cell fates in a dosedependent manner (Harland and Gerhart, 1997;Dosch et al, 1997). On the dorsal side, bmp expression is repressed by the homeodomain protein Bozozok (Boz, also called Dharma or Nieuwkoid; Koos and Ho, 1999;Fekany-Lee et al, 2000). In addition, organizer cells secrete Bmp inhibitors such as Chordin, Noggin, and Follistatin (Mullins, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Boz inhibits the ventralization of zebrafish by directly binding the bmp2b promoter and repressing its expression and by repressing the expression of vox/vega1, vent/vega2, and ved through an undetermined mechanism (Fekany et al, 1999;Koos and Ho, 1999;Kawahara et al, 2000a, b;Melby et al, 2000;Shimizu et al, 2002;Leung et al, 2003a). Boz can also induce ectopic expression of dpr1 and dpr2 (see above), but their expression does not require Boz signaling, as 100% of embryos from boz heterozygous crosses had wild-type dpr1 and dpr2 expression (n ϭ 133 for dpr1 and n ϭ 140 for dpr2; Fig.…”
Section: Dorsal Expression Of Dpr1 and Dpr2 Is Restricted By Bmp Signmentioning
confidence: 99%
“…␤-catenin cooperates with the HMG-box factor Tcf/Lef in activating the expression of some dorsal-specific genes, such as bozozok/dharma (boz) in zebrafish. Boz, directly regulated by ␤-catenin, is a transcriptional repressor, and its downstream targets include several genes that induce ventral specification or inhibit dorsal development (Yamanaka et al, 1998;Fekany et al, 1999;Koos and Ho, 1999). The zebrafish boz mutant shows defects in dorsoanterior embryonic structures and it has been reported that this factor promotes development of anterior neuroectoderm by inhibiting BMP and Wnt signaling (Solnica-Krezel and Driever, 2001).…”
Section: Introductionmentioning
confidence: 99%